(untitled) (Hekima Review, 2009)
The present essay tries to present the main features of mothering in present day Cameroon. Starting with traditional images drawn from Cameroonian and biblical traditions, the author shows that motherhood is held in high esteem in Cameroon. Then, he uses the feminist critique to show how the concept of mothering has been abused and used against women. The last part serves in surveying features as childrearing, transmission of values, danger of anonymity, and the dissociation between mothering and marriage.